Macro Importance of Micronutrients in Indian Agriculture - Shukla, Arvind Kumar; Tiwari, Pankaj Kumar; Singh, Pooja; Tiwari, K N (Indian Farming, 2017)
The present article deals with current status of micronutrient deficiencies in Indian soils, their deficiency symptoms, major sources of micronutrients and their effect on crops and best management practices to combat micronutrient deficiencies.